EFFECTIVENESS OF FOUR INSECTICIDES TO CONTROL CITRUS LEAFMINER (PHYLLOCNSTIS CITRELLA STAINTON) (LEPIDOPTERA: GRACILLARIDAE) ON ORANGE TREES AT RIVER NILE STATE, SUDAN - & Ali, Ali (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
The efficacies of four insecticides with two different formulations liquid and solid viz; two as foliar sprays, Match 050 EC (lufenuron) and Icaros 1.8% EC (abamectin) as well as soil drench of Actara 25% WG (thiamethoxam) and Furadan 10% G (carbofuran) to control citrus leafminer (CLM) in orange orchard located in River Nile State during winter seasons 2015and 2016. The experiment was assigned in a randomized complete block design (RCBD) with three replications. At each year two foliar and soil drench insecticidal were applied one time in late January. CLM larval counts were recorded at 3, 7, 14 and 21 days after treatment (DAT). Results showed that regardless the agricultural season and the time of all tested insecticidal application nearly almost suppressed in the number of CLM larvae compared to the untreated-control. At the 21st day after treatment (DAT), the insecticidal activities of all chemicals were declined. However, the two formulations, Actara and Furadan exhibited the highest residual activity more than three weeks compared to the tow foliar sprays by Icaros 1.8% EC or Match 050 EC. Thus, Actara 25% WG and Furadan10% G showed the higher soil drench insecticidal activity and persistence against CLM infestation on orange trees.